Population genetics and ecology of Sumatran camphor (Dryobalanops aromatica) in natural and community-owned forests in Indonesia - FAUJIAH NURHASANAH RITONGA; FIFI GUS DWIYANTI; CECEP KUSMANA; ULFAH JUNIARTI SIREGAR; ISKANDAR ZULKARNAEN SIREGAR (Society for Indonesian Biodiversity, 2018)
Ritonga FN, Dwiyanti FG, Kusmana C, Siregar UJ, Siregar IZ. 2018. Population genetics and ecology of Sumatran camphor (Dryobalanops aromatica) in natural and community-owned forests in Indonesia. Biodiversitas 19: 2175-2182. Dryobalanops aromatica Gaertn. f. (Sumatran camphor) is a valuable tree species that produces borneol (camphor) and good-quality timber. However, the population of this species has declined due to illegal logging and conversion of forests into plantations and has been classified as Critically Endangered by the International Union for Conservation of Nature. This study aimed to examine the genetic variation and spatial distribution of this species in a community-owned forest (Barus) and two natural forests (Singkohor and Danau Paris) in Indonesia using the Random Amplified Polymorphic DNA marker. The results of this study showed that D. aromatica had moderate levels of genetic variation (expected heterozygosity [He] = 0.1760 [Barus population] to 0.2134 [Singkohor population]) and genetic differentiation (Nei’s Gst = 0.1257). The genetic distance was the smallest between the Singkohor and Danau Paris populations (Nei’s distance = 0.0363) and greatest between the Singkohor and Barus populations (Nei’s distance = 0.0534). The spatial distribution of D. aromatica was grouped in both Barus and Danau Paris based on Morisita’s index of diversity (ip = 0.06 and 0.043, respectively). These findings indicated that genetic conservation might be performed in situ in combination with enrichment planting using locally propagated sources.